For this one, since the amounts in the parenthesis are being multiplied by x, you distribute x to all of the terms inside the parenthesis. When you do this, the problem looks like this:
x^2-5x=14
Now we have a quadratic, so we need to set the equation to 0. Subtract both sides by 14:
x^2-5x-14=0
We can then factor the trinomial:
(x-7)(x+2)=0
Now we just need to solve for x so that when we plug it into the equation, it will equal zero. We find that in the first binomial, if x=7 and we multiply it by whatever is in the second binomial, the answer is zero. By the same method, if x=-2 and we multiply
that by whatever is in the first binomial, the answer is zero. This means that x=7 and x=-2.